A fluorescence-based method to directly quantify antibodies immobilized on gold nanoparticles. Issue 12 (26th April 2016) - Filbrun, Seth L.; Driskell, Jeremy D.
Abstract : The ability to evaluate antibody immobilization onto gold nanoparticles is critical for assessing coupling chemistry and optimizing the sensitivity of nanoparticle-enabled biosensors. Abstract : The ability to evaluate antibody immobilization onto gold nanoparticles is critical for assessing coupling chemistry and optimizing the sensitivity of nanoparticle-enabled biosensors. Herein, we developed a fluorescence-based method for directly quantifying antibodies bound onto gold nanoparticles. Antibody-modified gold nanoparticles were treated with KI/I2 etchant to dissolve the gold nanoparticles. A desalting spin column was used to recover the antibody released from the nanoparticles, and NanoOrange, a fluorescent dye, was used to quantify the antibody. We determined 309 ± 93 antibodies adsorb onto a 60 nm gold nanoparticles (2.6 × 10 10 NP mL −1 ), which is consistent with a fully adsorbed monolayer based on the footprint of an IgG molecule. Moreover, the increase in hydrodynamic diameter of the conjugated nanoparticle (76 nm) compared to that of the unconjugated nanoparticle (62 nm) confirmed that multilayers did not form. A more conventional method of indirectly quantifying the adsorbed antibody by analysis of the supernatant overestimated the antibody surface coverage (660 ± 87 antibodies per nanoparticle); thus we propose the method described herein as a more accurate alternative to the conventional approach.